Peningkatan Kompetensi Pedagogik dan Profesionalitas Guru di Indonesia Melalui Pendidikan Profesi Guru (PPG) - Mardhatillah, Olivia; Surjanti, Jun (Universitas Pendidikan Ganesha, 2023)
Indonesian teachers is low. This is a problem that must be faced by educational institutions to review the implementation of PPG in improving teacher pedagogic competence and professionalism. This research was conducted by examining more deeply the report on the results of the implementation of teacher pedagogic competency and professionalism tests. This study also explains the teacher's pedagogic and professional competency maps and the urgency of the role of the PPG program in Indonesia in improving the quality of education. This study maps pedagogic and professional competence in the low, medium and high categories based on the balance of education from the results of teacher competency tests throughout Indonesia in 548 regions in Indonesia in order to describe teacher potential as a basic basis for analysis. An urgency analysis was carried out by comparing the competence of teachers before and after participating in PPG based on the data sources in the articles. Based on data that has been mapped, the pedagogic competence and professional competence of teachers in Indonesia are in the medium category. The results of the literacy study found that PPG has so far been able to improve teacher pedagogic and professional competence, so the implication of this paper is to provide a view for higher education institutions as PPG organizers to prepare programs that are able to improve pedagogic and professional competence through the involvement of government support to evaluate implementation PPG program in producing quality education.